Bibliometric Analysis of Digital Sustainability Marketing - Loso Judijanto; Rusdianto Rusdianto (West Science Social and Humanities Studies, 2026)
This study aims to map and analyze the intellectual structure, thematic evolution, and collaboration patterns of Digital Sustainability Marketing research through a bibliometric approach. Using data extracted from the Scopus database, the analysis was conducted with VOSviewer to examine keyword co-occurrence, overlay visualization, density mapping, co-authorship networks, institutional collaboration, and country-level partnerships. The findings reveal that sustainability, marketing, and sustainable development serve as the central pillars of the research field, reflecting a strong integration between environmental discourse and digital marketing strategies. Overlay analysis indicates a temporal shift from technology- and innovation-driven discussions toward more applied themes such as digital tools, consumer behaviour, and strategic marketing implementation. Density visualization highlights the growing concentration of research around digital transformation and electronic commerce, while collaboration analysis shows that although the field is globally distributed, research networks remain relatively fragmented across authors, institutions, and countries. Overall, the study provides a comprehensive overview of the evolution and current landscape of Digital Sustainability Marketing, offering insights into emerging trends and future research directions, particularly in data-driven marketing, SME innovation, and sustainable digital ecosystems.